Operations research for military organizations - Tozan, Hakan; Karatas, Mumtaz (Advances in logistics, operations, and management science (ALOMS) book series, 2019)
This book explores problems which incorporate every aspect of contemporary quantitative applications of operations research methods in military. It address and feature original research on the innovative applications of techniques and methodologies on defense and military related problems and relevant theoretical frameworks and the latest empirical research findings in the area.